Climate Analysis of Tornadoes in China - 姚叶青 俞小鼎 张义军 周自江 谢五三 卢燕宇 余金龙 魏凌翔 (Journal of Meteorological Research, 2015)
Based on analysis of historical tornado observation data provided by the primary network of national weather stations in China for the period from 1960 to 2009, it is found that most tornadoes in China （85%） occurred over plains. Specifically, large numbers of tornado occurrences are found in the Northeast Plain, the North China Plain, the middle-lower Yangtze Plain, and the Pearl River Delta Plain. A flat underlying surface is conducive to tornado occurrence, while the latitudal variation of tornado occurrence in China is not so obvious. Tornadoes mainly occur in summer, and the highest frequency is in July. Note that the beginning and the time span of tornado outbreaks are different in North and South China. Tornadoes occur during May-September in South China （south of 25°N）, June-September in Northeast China （north of 40°N）, July-September in the middle-lower Yangtze Plain, and July-August in North China （between 25° and 40°N）. More than 80% of total tornadoes occurred during the above periods for the specific regions. The 1960s and 1970s have seen about twice the average number of tornadoes （7.5 times per year） compared to the mean for 1960-2009. The most frequent occurrence of tornado was in the early and mid 1960s; there were large fluctuations in the 1970s; and the number of tornadoes in the 1980s approached the 50-yr average. Tornado occurrences gradually decreased in the late 1980s, and an abrupt change with dramatic decrease occurred in 1994. The decrease in the tornado occurrence frequency is consistent with the simultaneous climatic change in the meteorological elements that are favorable for tornado formation. Tornado formation requires large vertical wind shear and sufficient atmospheric moisture content near the ground. Changes in the vertical wind shear at both 0-1 and 0-6 km appear to be one important factor that results in the decrease in tornado formation. The changing tendency of relative humidity also has contributed to the decrease in tornado formation in China.